The hydration effect on reactive silica concrete containing eggshell powder - Muhamad Fekry Murhazan, 1994- , author; Hafizah Abd. Khalid, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017